(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2023)
E-government has many benefits at the level of individuals and governments. Most governments began to exploit information and communication technologies to provide information and services to their citizens. Despite the great role and the many benefits of e-government applications, many studies indicate that a large proportion of initiatives to implement E-government around the world failed in achieving the promised goals. Most e-government projects in developing countries have partially or totally failed. Adoption and use of e-services is still rather limited in most countries. The growing attention paid by governments to invest in e-government projects and the lack of e-services usage refer to a gap between the real needs and expectations of users and the actual use and satisfaction. Responding to the high rates of failure and low rates of usage, the researchers were motivated to find new ways to reduce this gap and maximize the impact of investment in such projects. The aim of this paper is to propose a novel approach for eliciting users’ needs and requirements for e-government projects.